Faktor Faktor Pendorong dan Penghambat Keinginan Petani Melakukan Peremajaan Kelapa Sawit di Desa Suka Damai Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat - Handayani, Putri; Zainuddin, Zainuddin; Wulandari, Siti Abir (Jurnal MeA (Media Agribisnis), 2024)
The purpose of this study was to analyze the factors that encourage and inhibit farmers' desire to replant oil palm trees in Suka Damai Village, Tebing Tinggi Sub-district, Tanjung Jabung Barat District. The research was conducted as a survey of farmers in Suka Damai Village with the criteria that the age of oil palm plants is more than 20 years old and technically feasible to replant. A sample of 108 farmers was taken from a population of 540 oil palm farmers using the simple random method. The research data were analyzed using a regression model with the dependent variable measured binary. The results showed that land size, number of family members, gross income from oil palm farming, and total household expenditure influenced farmers' willingness to replant. Farmer age, formal education, age of the oil palm plantation, and access to credit loans do not influence farmers' desire to replant oil palm. Factors driving farmers' desire to replant oil palm crops are variables of oil palm land area, number of farmer family members, and gross oil palm farm income, while the inhibiting factor is the total expenditure of farmer households.